Gastric Ulceration Occurring during Indomethacin Therapy - Taylor, R. T. (1968)
Dyspeptic symptoms, gastrointestinal bleeding, or the development of anaemia without dyspepsia in patients treated with indomethacin may be manifestations of peptic ulceration. Such manifestations occur with suppositories as well as with capsules. The ulcers in the present series tended to be prepyloric, and often aroused the suspicion of malignancy. Symptoms were promptly relieved and radiological healing occurred rapidly after withdrawal of the drug.